Mechanism of microplastics in respiratory disease from 2020 to 2024: visualization and bibliometric analysis - Zixi Du; Xia Yu; Xue Li; Ling Zhang; Yonghong Lin; Yulei He; Ying Wu (Frontiers in Medicine)
ObjectiveThe effect of microplastics (MPs) on the respiratory disease is extremely significant. Targeted intervention can be aided by recognizing the pathophysiology of microplastics in respiratory diseases. This research attempts to identify major trends in literatures and highlight key research based on bibliometric analysis to figure out present research areas and potential future research directions.MethodsRelevant academic works from 2020 to 2024 were downloaded from the Web of Science Core Collection (WoSCC). Subsequent examination of these records was performed utilizing multiple analytical tools: The R statistical package (version 4.3.2), CiteSpace software, the online analysis platform of Literature Metrology and the online interface of bibliometrix.1ResultsA total of 78 qualified records were identified and included in the analysis. China has the highest number of publications. The most referenced journal was Science of the Total Environment. Chinese Academy of Sciences was the institution with the highest publication number. Toxicity, ingestion, accumulation, metabolism, gene, oxidative stress, inflammation and cell death were among the 25 most relevant terms.ConclusionResearch on the processes of MPs in the respiratory disease has advanced rapidly during the past 5 years. Human exposure (toxicity, ingestion, accumulation and metabolism), gene, oxidative stress, inflammation and cell death are the five main research area. In the following stage, deep studies on the connection of various mechanisms will be conducted, and efforts are expected to minimize the level of MPs in the human body, thus reducing the risk to humans.